2016
DOI: 10.1007/s10620-016-4234-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Bone Marrow-Derived CD45−/CD34+/CD133+/VEGF+ Endothelial Progenitor Cells in Adults with Crohn’s Disease

Abstract: EPCs are elevated in patients with CD. Further studies are needed to examine the function of EPCs and their possible role as a marker of disease severity or therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…In fact, Galiano et al [13] reported that a local elevated level of VEGF and SDF-1 in ischemic foci may help in EPC recruitment from the circulation to the site of injury to assist diabetic wound healing. Therefore, it is highly likely that an increase in peripheral EPCs may be a sign of treatment feedback, though the authors could not support this association in their study [11]. The present study [11] presents a major advantage over previous studies in terms of clinical variables and number of patients.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…In fact, Galiano et al [13] reported that a local elevated level of VEGF and SDF-1 in ischemic foci may help in EPC recruitment from the circulation to the site of injury to assist diabetic wound healing. Therefore, it is highly likely that an increase in peripheral EPCs may be a sign of treatment feedback, though the authors could not support this association in their study [11]. The present study [11] presents a major advantage over previous studies in terms of clinical variables and number of patients.…”
mentioning
confidence: 55%
“…Boltin et al's [11] findings mark an important step toward addressing the current controversies in CD research. Their results are consistent with accumulating evidence that EPCs do in fact participate in the regeneration of damaged epithelium.…”
mentioning
confidence: 92%
See 3 more Smart Citations